3-O-(E)-p-coumaroyl tormentic acid from Eriobotrya japonica leaves induces caspase-dependent apoptotic cell death in human leukemia cell line - Takashi Kikuchi (2018)
Eleven triterpene acids, 1-11, isolated from the leaves of Eriobotrya japonica, were evaluated for inhibition of DNA topoisomerase (Topo) I and cytotoxicity against human leukemia (HL60) and melanoma cell lines (CRL1579). Among the compounds tested, four compounds, d-oleanolic acid (4), ursolic acid (5), 3-O-(E)-p-coumaroyl tormentic acid (8), and betulinic acid (10), exhibited potent Topo I inhibitory activity (IC5020.3-36.5 μM) and cytotoxicity against HL60 (EC505.0-8.1 μM). Upon assessing the apoptosis-inducing activity in. HL60 cells, compound 8 exhibited induction of apoptosis detected by the observation of DNA fragmentation and membrane phospholipid exposure in flow cytometry. Western blot analysis showed that compound 8 markedly reduced the levels of procaspases-3 and 9, while being increased the levels of cleaved caspases-3 and 9. On the other hand, compound 8 exerted almost no influence on the expression of caspase-8. In addition, compound 8 increased significantly Bax/Bcl-2 ratio and activated caspase-2. These results suggested that compound 8 induced apoptotic cell death in HL60 via mainly mitochondrial pathway by, at least in part, Topo I inhibition. Therefore, compound 8 may be promising lead compound for developing an effective drug for treatment of leukemia. © 2011 Pharmaceutical Society of Japan.